2002
DOI: 10.1292/jvms.64.1173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Infusion of Isotonic Sodium Bicarbonate Solution on Acidemic Calves with Diarrhea.

Abstract: ABSTRACT. The effect of 1.35% isotonic sodium bicarbonate solution (ISB) administered intravenously on acid-base equilibrium was examined in 18 acidemic Japanese black beef calves with spontaneous diarrhea. The infusion volumes of ISB were decided based on the first half volumes of base needed. In 72.2% (13/18) of calves, improvement of acidemia was detected. There was good correlation (r=0.693, p<0.01) between infused volume of ISB and changes in base excess (y=1.097x + 4.762). Infusion volumes of ISB were 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…It has been recommended that the first half of the calculated dose of sodium bicarbonate solution should be administered rapidly [2]. Furthermore, a previous study demonstrated that infusion volume of ISB was 10.2 ml/kg, enough to correct the first half of the 10 mEq/l the of base deficit in acidemic calves [16]. In this study, therefore, the calves in the ISB and HSB groups were given an IV infusion of 5 mM ISB (10.0 ml/kg) or HSB (1.9 ml/kg) via the left jugular catheter over a 15 min period, with an infusion pump (PRS-25, Nikkiso Co., Tokyo, Japan).…”
mentioning
confidence: 99%
“…It has been recommended that the first half of the calculated dose of sodium bicarbonate solution should be administered rapidly [2]. Furthermore, a previous study demonstrated that infusion volume of ISB was 10.2 ml/kg, enough to correct the first half of the 10 mEq/l the of base deficit in acidemic calves [16]. In this study, therefore, the calves in the ISB and HSB groups were given an IV infusion of 5 mM ISB (10.0 ml/kg) or HSB (1.9 ml/kg) via the left jugular catheter over a 15 min period, with an infusion pump (PRS-25, Nikkiso Co., Tokyo, Japan).…”
mentioning
confidence: 99%
“…If a serum bicarbonate is available, bicarbonate requirements can be calculated from the bicarbonatemia, using the following formula with a Vd of 0.6 (to compensate for buffering by non-bicarbonate systems) (Suzuki et al, 2002;Naylor et al, 2006).…”
Section: Sodium Bicarbonate Requirement Mmol = Body Weight Kg X Basmentioning
confidence: 99%
“…Normally the correction of acidosis requires 1 to 4 L (25 to 100 mL kg −1 ) of an isotonic solution of sodium bicarbonate (1.3%), administered intravenously over about 4 to 8 h (Suzuki et al, 2002;Naylor et al, 2006). It is possible that this rapid correction produces a paradoxical CSF acidosis.…”
Section: Sodium Bicarbonate Requirement Mmol = Body Weight Kg X Basmentioning
confidence: 99%
“…If treatment with oral fluids is unsuccessful, intravenous restoration for the acid-base disorder is performed [6][7][8]. Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16]. Sodium bicarbonate is specifically effective for acute and severe metabolic acidosis because it has rapid effect when given intravenously [7,9,15,16].…”
mentioning
confidence: 99%
“…Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16]. Sodium bicarbonate is specifically effective for acute and severe metabolic acidosis because it has rapid effect when given intravenously [7,9,15,16]. Nevertheless, rapid administration or an overdose of sodium bicarbonate solution has been associated with paradoxical cerebrospinal fulid acidosis, leftward shift of the oxyhemoglobin dissociation curve leading to decreased downloading of oxygen, intracellular shift of potassium in exchange for hydrogen ions causing hypokalemia, tetany due to decreased ionized calcium, and overshot alkalosis [2,5].…”
mentioning
confidence: 99%